Alcohol health literacy in young adults with Type 1 diabetes and its impact on diabetes management. Issue 12 (7th June 2014) - Barnard, K. D.; Dyson, P.; Sinclair, J. M. A.; Lawton, J.; Anthony, D.; Cranston, M.; Holt, R. I. G.
Abstract Aims To investigate the knowledge of alcohol and carbohydrate content of commonly consumed alcoholic drinks among young adults with Type 1 diabetes and to explore alcohol consumption while identifying diabetes self‐management strategies used to minimize alcohol‐associated risk. Method We conducted an open‐access, multiple‐choice web survey to investigate knowledge of alcohol and carbohydrate content of typical alcoholic drinks using images. Respondents to the survey also recorded their current alcohol consumption and diabetes self‐management strategies when drinking. Results A total of 547 people aged 18–30 years responded to the survey (341 women; 192 men; mean (sd) age 24.5 (3.7) years), of whom 365 (66.7%) drank alcohol. In all, 84 (32.9%) women and 31 (22.6%) men scored higher than the cut‐off score for increased‐risk drinking. Knowledge accuracy of alcohol units was poor: only 7.3% (n = 40) correctly identified the alcohol content of six or more out of 10 drinks. Knowledge of carbohydrate content was also poor: no respondent correctly identified the carbohydrate content of six or more out of 10 drinks. Various and inconsistent strategies to minimize alcohol‐associated risk were reported. Conclusions Alcohol consumption was common among the survey respondents, but knowledge of alcohol and carbohydrate content was poor. Greater alcohol‐related health literacy is required to minimize alcohol‐associated risk. Further research should help develop effective strategies to improve health literacy and support safe drinking for young adults with Type 1 diabetes.